1997
DOI: 10.2355/isijinternational.37.946
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Agglomeration of Various Inclusion Particles on Molten Steel Surface.

Abstract: Miyagi-ken, The behavior of various inclusion particles at inert gaslmolten steel interface was "in-situ" studied with a confocal scanning laser microscope, Solid CaO-AI203and solid CaO-Al203-Si02inclusion particles were subjected to quick agglomeration to form clusters which densified and deformed later. Capillary attraction was found responsible for the agglomeration and densification. The capillary effect also operated between solid CaO-AI203inclusion particle and liquid CaO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
129
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(134 citation statements)
references
References 1 publication
4
129
0
1
Order By: Relevance
“…Arai et al 24) reported that the particles with the large contact angle against the solvent easily attach to the bubbles and are more likely to be removed. Yin et al 40) and Wikström et al 41) observed the inclusion behavior at the metal/gas interface reporting that attraction force was applied between the solid inclusions which are not wet with the molten steel. On the other hand, attraction force was not applied between the liquid inclusions which can intimately wet with the molten steel.…”
Section: Rh Treatmentmentioning
confidence: 99%
“…Arai et al 24) reported that the particles with the large contact angle against the solvent easily attach to the bubbles and are more likely to be removed. Yin et al 40) and Wikström et al 41) observed the inclusion behavior at the metal/gas interface reporting that attraction force was applied between the solid inclusions which are not wet with the molten steel. On the other hand, attraction force was not applied between the liquid inclusions which can intimately wet with the molten steel.…”
Section: Rh Treatmentmentioning
confidence: 99%
“…Professor Toshihiko Emi pioneered the use of laser confocal optics with an Au-image furnace allowing for in situ imaging, and his group at Tohoku University was the first to document the clustering of inclusions, [36,37] peritectic solidification, [38] and particle pushing. [39] The present work, inspired by Prof. Emi's stellar publications, leads on from the initial findings of Assis et al, [1] where high-temperature confocal scanning laser microscopy (HT-CSLM) and micro X-ray computer tomography (XCT) were coupled together to provide insight into the full transient morphology of an Fe-P 0.2 wt pct alloy droplet submerged in slag similar to that seen in end blow BOF refining.…”
Section: Introductionmentioning
confidence: 99%
“…[99,129,130] Several methods determine the threedimensional inclusion size distributions after the inclusions are extracted from the steel: Coulter counter analysis, [131] photoscattering method, [106,132] and laser-diffraction particle size analyzer. [109] Several methods directly detect the inclusion amount and size distribution in the molten melt: ultrasonic techniques for the liquid system, [104,[133][134][135] liquid metal cleanliness analyzer, [135,136] confocal scanning laser microscope, [137,138,139] and electromagnetic visualization. [140] B.…”
Section: Methods To Detect Inclusionsmentioning
confidence: 99%